2021
DOI: 10.1002/adem.202101264
|View full text |Cite
|
Sign up to set email alerts
|

Coatings for Core–Shell Composite Micro‐Lattice Structures: Varying Sputtering Parameters

Abstract: Magnetron sputtering has garnered increased attention as a versatile deposition method for generating novel core–shell composite nano‐ and micro‐lattice materials spanning a wide range of properties and functionalities. Sputtering offers an expansive material workspace consisting of a wide range of ceramics, single‐element metals, and alloy systems. However, achieving uniform coatings on such fine‐featured structures remains a challenge. Thus, herein, a foundational assessment of various sputtering configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…To a lesser extent, some studies have investigated ICM sputtering within the cathode volume, analyzing coating wires and adhesion [15,16,[25][26][27]. Furthermore, a few studies have explored this target geometry as an alternate deposition configuration for coating substrates with convoluted complex topologies [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent, some studies have investigated ICM sputtering within the cathode volume, analyzing coating wires and adhesion [15,16,[25][26][27]. Furthermore, a few studies have explored this target geometry as an alternate deposition configuration for coating substrates with convoluted complex topologies [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In general, sputter coated nano-and micro-lattices have mostly employed planar target geometries and focused on the coated lattice material properties; some studies have also investigated coating uniformity and observed thickness gradients resulting from the unidirectional deposition of the planar cathode [31][32][33][34]. Garcia-Taormina et al demonstrated using a hollow cathode that changing target geometry could potentially improve coating coverage on micro-lattice structures by increasing line-of-sight during deposition [28]. Thus, in order to enable further exploration of deposition within complex target geometries, such as the hollow cathode, the correlations between cathode geometry and film growth warrant further research.…”
Section: Introductionmentioning
confidence: 99%